International regulatory changes in financial systems as a factor of stability - Anevski, Dimitar; Temelkovska-Anevska, Elena (The European Journal of Applied Economics, 2017)
The necessity of regulation to certain legal and finance systems derives from the possibility that they may have a major impact on the essential processes in the countries. Therefore, depending on the market conditions and integration intentions to specific political or financial groups, the countries are forced to implement new regulations. Regulation is different everywhere in the world; there are hundreds of laws and legal acts arising from national and local governments, which cover various aspects of the economy. The paper examines the international capital agreements and legal acts responsible for the stability of the finance sector and its members, which lead to overall stability of society. Analyzing the contemporary literature reveals the countries which successfully have managed to implement the high demanding criteria.